2020
DOI: 10.1371/journal.pntd.0008109
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian phase 2 model based adaptive design to optimise antivenom dosing: Application to a dose-finding trial for a novel Russell’s viper antivenom in Myanmar

Abstract: For most antivenoms there is little information from clinical studies to infer the relationship between dose and efficacy or dose and toxicity. Antivenom dose-finding studies usually recruit too few patients (e.g. fewer than 20) relative to clinically significant event rates (e.g. 5%). Model based adaptive dose-finding studies make efficient use of accrued patient data by using information across dosing levels, and converge rapidly to the contextually defined ‘optimal dose’. Adequate sample sizes for adaptive … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Independent analysis has shown that manufacturers’ dose recommendations are often unrealistic, and lack of published supporting data reinforces this view ( Calvete et al, 2016 ; Harrison et al, 2017 ). Antivenoms should not be given registration or marketing authorization by national regulatory authorities in the absence of independent preclinical neutralization tests and well-designed, pragmatic clinical dose-finding and safety studies ( Williams et al, 2018 ; Watson, 2020 ). For healthcare providers and drug regulatory agencies to be able to determine the effective clinical dose of a given product, the amount of venom that is completely neutralized by a milliliter of antivenom should be indicated.…”
Section: Upstream: Randd and Innovation/manufacturingmentioning
confidence: 99%
“…Independent analysis has shown that manufacturers’ dose recommendations are often unrealistic, and lack of published supporting data reinforces this view ( Calvete et al, 2016 ; Harrison et al, 2017 ). Antivenoms should not be given registration or marketing authorization by national regulatory authorities in the absence of independent preclinical neutralization tests and well-designed, pragmatic clinical dose-finding and safety studies ( Williams et al, 2018 ; Watson, 2020 ). For healthcare providers and drug regulatory agencies to be able to determine the effective clinical dose of a given product, the amount of venom that is completely neutralized by a milliliter of antivenom should be indicated.…”
Section: Upstream: Randd and Innovation/manufacturingmentioning
confidence: 99%
“…Robust clinical data on the safe and effective initial dose of antivenom are lacking for most products. 102 Clinicians often rely on manufacturers’ recommendations provided as package inserts or labels, but these can be unreliable. 103 104 We suggest following national protocols or standard regional guidelines for dose.…”
Section: How Is Snakebite Managed?mentioning
confidence: 99%
“…The risks of anaphylaxis and sensitisation to animal proteins in antivenoms place ethical limitations on conventional phase I/II designs. 124 Some literature suggests that model based adaptive designs, as used to test anticancer drugs, could be safer alternatives for antivenom testing 95 102 124 …”
Section: What Are the Long-term Sequelae Of Snakebite?mentioning
confidence: 99%
“…The method has, however, been criticized ( Chippaux and Boyer, 2010 ), and modifications entailing commencement with a higher dose followed by subsequent de-escalation have been suggested, especially following presynaptic neurotoxic envenomings, where clinical manifestations may be irreversible and should be timely prevented. Recently, a Bayesian model-based adaptive design has been suggested to be more efficient and has the capacity to enroll larger patient sample sizes determined by simulations ( Watson et al, 2020 ). This is also more flexible and has better operating characteristics than the CRM.…”
Section: Repositioning Conventional Antivenom Therapymentioning
confidence: 99%
“…Both approaches are suitable for safety and efficacy assessments with binary outcomes. The adaptive design was developed to be used to determine the optimal safe and effective dose of a new antivenom used to treat Russell's viper envenoming in Myanmar and will probably be increasingly used to introduce antivenoms into clinical management ( Watson et al, 2020 ).…”
Section: Repositioning Conventional Antivenom Therapymentioning
confidence: 99%